PENERAPAN TEKNIK BERMAIN PERAN DALAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI SEKOLAH DASAR - Febri Pabenjanan; Tesalonika (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to analyze the effectiveness of using role-playing techniques in group guidance services to increase the self-confidence of elementary school students. The background of this research is based on the low level of self-confidence in students, which is evident in shyness, a lack of courage in expressing opinions, and minimal involvement in the learning process. Therefore, a creative, engaging, and enjoyable method is needed to enable students to develop their full potential. This study used a literature review method by collecting and reviewing various relevant literature sources, such as books, scientific journals, and previous research related to group guidance, role-playing techniques, and elementary school students' self-confidence. Data were analyzed using qualitative content analysis techniques through the stages of data reduction, grouping, and interpretation. The results of the study indicate that the application of role-playing techniques in group guidance has a significant impact on increasing student self-confidence. Through role-playing activities, students become more confident in expressing themselves, their communication skills improve, their cooperation among students develops, and their independence is enhanced. Furthermore, this approach also creates an active, participatory, and enjoyable learning environment. Thus, it can be concluded that role-playing techniques in group guidance are an effective strategy for increasing elementary school students' self-confidence. This research is expected to contribute to the development of guidance and counseling practices and learning innovations in elementary school settings.